Inside Back Cover: Aqueous Biphasic Systems for the Synthesis of Formates by Catalytic CO2 Hydrogenation: Integrated Reaction and Catalyst Separation for CO2‐Scrubbing Solutions (ChemSusChem 6/2017). Issue 6 (21st March 2017) - Scott, Martin; Blas Molinos, Beatriz; Westhues, Christian; Franciò, Giancarlo; Leitner, Walter
Abstract : The Inside Back Cover picture shows the direct hydrogenation of CO2 saturated aqueous scrubbing solutions to formate adducts in a biphasic system using a ruthenium catalyst. More details can be found in the Full Paper by Scott et al. onpage 1085 in Issue 6, 2017 (DOI:10.1002/cssc.201601814 ).